Neuro-Spirituality and the Universal Consciousness Field: Reframing the Brain as Receiver, Transmitter, and Filter - Umar Wyne (`, 2025)
Most arguments about spirituality still transport between two opposites: either purely religious language that depends on faith and doctrine, or purely materialistic language that tries to reduce everything to brain chemistry. This paper proposes a third way, which I call Neuro-Spirituality. It treats spirituality as a real dimension of human consciousness that can be studied through neuroscience, psychology, quantum biology, and philosophy of mind without getting trapped in dogma. The premise is that the human brain does not simply “produce” consciousness like a machine that outputs a signal, instead, the brain functions as a receiver, transmitter, and filter of a broader Universal Consciousness Field—a non-local field of information and awareness. This idea has old philosophical echoes in concepts like Purusha in Samkhya, Noor-e-Muhammad in some Islamic metaphysics, and more recent scientific speculation in the work of James, Jung, Bohm, Penrose, Newberg, and others.[1–7] But here I try to pull it together in a more systematic and testable way. Methodologically, the paper is a conceptual and integrative study that reviews key literature from neuroscience, quantum physics, genetics, epigenetics, anthropology of religion, and consciousness research which then builds a structured model of Neuro-Spirituality. The results are presented as a theoretical framework and a practical methodology that can later be tested empirically in mental health, creativity, and personal transformation work. The aim is not to substantiate any religious claim or deny spiritual experience but to reframe spirituality as a natural—though still mysterious—expression of human participation in a Universal Consciousness Field. Keywords: Neuro-Spirituality; Universal Consciousness Field; brain as receiver; consciousness; quantum biology; non-religious spirituality